Pendampingan Keberlanjutan UMKM dalam Meningkatkan Kesejahteraan Ekonomi di Kecamatan Babelan Kabupaten Bekasi: MSME Sustainability Assistance in Improving Economic Welfare in Babelan District, Bekasi Regency - Ria, Ria; Digdowiseiso, Kumba (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
In this study, we conducted a mini survey and interviews with MSME actors in Babelan District, Bekasi Regency, to identify the challenges they face in understanding and implementing sustainability reporting. The survey revealed several issues commonly encountered by MSMEs in the region regarding sustainability reporting. In response to the identified challenges, we initiated a dissemination activity aimed at enhancing the understanding of MSMEs in Babelan District, Bekasi Regency, regarding sustainability reporting. The method used in this community service is Community Based Research (CBR) using the Forum Group Discussion (FGD) approach in training, mentoring, and consultation. The primary goal of this activity is to provide MSMEs with the necessary tools and knowledge to create sustainability reports that can help them effectively manage their business operations and promote sustainability. By addressing the needs of MSMEs for accessible and relevant sustainability reporting, we aim to contribute to the improvement of economic welfare in Babelan District, Bekasi Regency. Empowering MSMEs with the capacity to embrace responsible business practices can lead to more sustainable and resilient enterprises, benefitting not only the businesses themselves but also the local community and environment. In conclusion, the dissemination of MSME sustainability reporting serves as a critical step towards achieving sustainable and responsible business practices. This activity strives to support the growth and development of MSMEs, ensuring their long-term success and positive impact on the economy and society at large.